The electrical activity of cardiac tissue via finite element method (2012)
For the treatment of certain cardiac disorders sometimes electrical currents are used as therapy, as it happens when fibrillation. This phenomenon manifest itself with chaotic and accelerated heart rhythm, preventing the pumping of blood to the rest the organism. In considering this type of heart disease, introduce mathematical models to analyze the dynamics and behavior of these discharges, in particular, bidomain model is one of the most studied in order to understand the electrical process in cardiac tissue as a phenomenon that can be mathematically modeled.